Abrasive pad

CN122995925APending Publication Date: 2026-10-27FUJIBO HLDG
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202580023286.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2024-03-27
Filing Date
2025-03-27
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

然而,近年来,随着半导体元件的配线的微细化,在对高度不同的阶差混合存在的被研磨物进行研磨时,在现有的研磨垫中,有时阶差消除性能或平坦化性能不充分,作为高分子量多元醇,正在研究使用PTMG以外的材料

Benefits of technology

[0038]认为在将湿润状态下的通过脉冲NMR法测定而得的研磨层的结晶相的含有比例与非晶相的含有比例的比调整为特定的范围的情况下,运动性高的非晶相的比例比结晶相或中间相多,研磨层在研磨中适度软化,由此成为即便在高度不同的阶差混合存在的被研磨物中阶差消除性能及平坦化性能也优异的研磨垫。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN122995925A_ABST
    Figure CN122995925A_ABST
Patent Text Reader

Abstract

The present invention aims to provide a polishing pad having excellent step-removing performance and planarizing performance. A polishing pad having a polishing layer containing a polyurethane resin foam, the polyurethane resin foam using an isocyanate-terminated prepolymer and a hardener as raw materials, the polishing pad characterized in that the ratio of the content ratio of crystalline phase to the content ratio of amorphous phase in the polishing layer measured by pulsed NMR method at 40°C in a wet state is 0.5 or more and 1.0 or less, and the ratio of the content ratio of intermediate phase to the content ratio of amorphous phase in the polishing layer measured by pulsed NMR method at 40°C in a wet state is 0.4 or more and 0.9 or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to a polishing pad. The polishing pad of this invention is used for polishing optical materials, semiconductor components, glass substrates for hard disks, etc., and is particularly suitable for polishing components on semiconductor wafers with oxide layers, metal layers, etc. Background Technology

[0002] Chemical mechanical polishing (CMP) is a commonly used polishing method for planarizing the surfaces of optical materials, semiconductor wafers, semiconductor components, and hard disk substrates.

[0003] use Figure 1 The CMP method will be explained. For example... Figure 1 Thus, the grinding apparatus 1 for performing the CMP method includes a grinding pad 3, which is held in place by a retaining ring in a manner that prevents the pressure plate 16 and the workpiece 8 from shifting. Figure 1 The grinding pad 3 (not shown) abuts against the workpiece 8 and includes a grinding layer 4 as the grinding layer and a buffer layer 6 supporting the grinding layer 4. The grinding pad 3 is rotated while the workpiece 8 is pressed, thereby grinding the workpiece 8. At this time, a slurry 9 is supplied between the grinding pad 3 and the workpiece 8. The slurry 9 is a mixture (dispersion) of water and various chemical components or hard, fine abrasive particles. The grinding effect is enhanced by the relative movement of the chemical components or abrasive particles with the workpiece 8 while flowing. The slurry 9 is supplied to the grinding surface through a groove or hole and then discharged.

[0004] Furthermore, in the polishing of semiconductor components, polishing pads using rigid polyurethane materials as polishing layers are commonly employed. These rigid polyurethane materials are obtained by reacting a prepolymer containing isocyanate components (such as toluene diisocyanate (TDI)) and high molecular weight polyols (such as polyoxytetramethylene glycol (PTMG)) with a diamine-based curing agent (such as 4,4'-methylenebis(2-chloroaniline) (3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA))). Since then, PTMG, which forms soft segments of urethane and exhibits ease of handling or moderate rubber elasticity, has frequently been used as the high molecular weight polyol in the prepolymer. However, in recent years, with the miniaturization of semiconductor device wiring, when polishing objects with mixed steps of varying heights, the existing polishing pads sometimes have insufficient step elimination or planarization performance. As a high molecular weight polyol, materials other than PTMG are being investigated.

[0005] Patent document 1 discloses an abrasive pad in which the defect rate is reduced by using a mixture of polypropylene glycol (PPG) and PTMG as a high molecular weight polyol prepolymer.

[0006] Existing technical documents

[0007] Patent documents

[0008] Patent Document 1: Japanese Patent Application Publication No. 2011-040737 Summary of the Invention

[0009] The problem that the invention aims to solve

[0010] However, the abrasive pad described in Patent Document 1 does not have sufficient step elimination and flattening performance because it uses a mixture of PPG and PTMG.

[0011] The present invention is made in view of the aforementioned problems, and aims to provide a polishing pad with excellent step difference elimination performance and planarization performance.

[0012] Technical means to solve the problem

[0013] The inventors have discovered a grinding pad comprising a grinding layer, wherein the ratio of the crystalline phase to the amorphous phase and the ratio of the intermediate phase to the amorphous phase in the grinding layer, as determined by pulsed nuclear magnetic resonance (NMR) in a wet state, are adjusted to achieve excellent step elimination and planarization performance when grinding a workpiece containing a mixture of steps of varying heights. This invention thus completes the present invention.

[0014] Furthermore, the inventors discovered that when the abrasive layer changes from a dry state to a wet state, the content ratio of the intermediate phase changes little, while the content ratio of the amorphous phase in the abrasive layer increases. Under specific conditions of changes in the intermediate phase and the amorphous phase in the abrasive layer, an abrasive pad that can solve the aforementioned problem can be obtained, thus completing the present invention.

[0015] That is, the present invention includes the following.

[0016] [1] An abrasive pad having an abrasive layer comprising a polyurethane resin foam, wherein the polyurethane resin foam is made from isocyanate-terminated prepolymer and a hardener, the abrasive pad being characterized in that:

[0017] The ratio of the crystalline phase content (%) to the amorphous phase content (%) in the polished layer, as determined by pulsed NMR at 40°C in a wet state, is 0.5 or more and 1.0 or less.

[0018] The ratio of the percentage of intermediate phase to the percentage of amorphous phase in the polished layer under the wetted state, as determined by pulsed NMR at 40°C, is 0.4 or more and 0.9 or less.

[0019] [2] According to the abrasive pad described in [1], the content of the amorphous phase in the abrasive layer, as determined by pulse NMR at 40°C in the wet state, is 30.0% or more and 55.0% or less.

[0020] [3] According to the abrasive pad described in [1], the content of the intermediate phase in the abrasive layer, as determined by pulse NMR at 40°C in the wet state, is 15.0% or more and 35.0% or less.

[0021] [4] According to the abrasive pad of [1], the isocyanate-terminated prepolymer comprises constituent units derived from polyisocyanate compounds and constituent units derived from high molecular weight polyols, wherein the constituent units derived from high molecular weight polyols comprise at least constituent units derived from polyester diols and constituent units derived from PTMG.

[0022] [5] The abrasive pad according to [4], wherein the number of polyester diols used to form the constituent units derived from polyester diol has an average molecular weight of 600 or more and 2500 or less.

[0023] [6] According to the abrasive pad of [4], the constituent units derived from PTMG are 30% or more and 80% or less by weight relative to the constituent units derived from high molecular weight polyols.

[0024] [7] According to the abrasive pad of [4], wherein the polyurethane resin foam uses at least two isocyanate-terminated prepolymers as raw materials, at least one of the at least two isocyanate-terminated prepolymers contains the constituent unit derived from PTMG, and the isocyanate-terminated prepolymer containing the constituent unit derived from PTMG has an NCO equivalent of 400 or more and 500 or less.

[0025] [8] According to the abrasive pad of [4], wherein the polyurethane resin foam uses at least two isocyanate-terminated prepolymers as raw materials, at least one of the at least two isocyanate-terminated prepolymers contains the constituent unit derived from polyester glycol, and the isocyanate-terminated prepolymer containing the polyester glycol constituent unit has an NCO equivalent of 550 or more and 700 or less.

[0026] [9] An abrasive pad having an abrasive layer comprising a polyurethane resin foam, wherein the polyurethane resin foam is made from isocyanate-terminated prepolymer and a hardener, wherein the abrasive pad,

[0027] The value obtained by subtracting the percentage of the intermediate phase in the polished layer measured by pulsed NMR at 40°C in the dry state from the percentage of the intermediate phase in the wet state is -2.0% or more and 2.0% or less.

[0028] The value obtained by subtracting the percentage of amorphous phase in the polished layer measured by pulse NMR at 40°C in the wet state from the percentage of amorphous phase in the polished layer measured by pulse NMR at 40°C in the dry state is 2.0% or more and 5.7% or less.

[0029]

[10] According to the abrasive pad described in [9], the proportion of crystalline phase in the abrasive layer, as determined by pulse NMR at 40°C in the wet state, is smaller than the proportion of amorphous phase.

[0030]

[11] According to the abrasive pad of [9], the content of the amorphous phase in the abrasive layer, as determined by pulse NMR at 40°C in the wet state, is 30.0% or more and 55.0% or less.

[0031]

[12] According to the abrasive pad described in [9], the content of the amorphous phase in the abrasive layer in the dry state, as determined by pulse NMR at 40°C, is 30.0% or more and 50.0% or less.

[0032]

[13] According to the abrasive pad of [9], the isocyanate-terminated prepolymer comprises constituent units derived from polyisocyanate compounds and constituent units derived from high molecular weight polyols, the constituent units derived from high molecular weight polyols comprising constituent units derived from polyester diols and constituent units derived from PTMG.

[0033]

[14] The abrasive pad according to

[13] wherein the number of polyester diols used to form the constituent units derived from polyester diol has an average molecular weight of 600 or more and 2500 or less.

[0034]

[15] The abrasive pad according to

[13] , wherein the PTMG constituent unit is 30% or more and 80% or less relative to the constituent unit derived from the high molecular weight polyol.

[0035]

[16] According to the abrasive pad of

[13] , wherein the polyurethane resin foam uses at least two isocyanate-terminated prepolymers as raw materials, at least one of the at least two isocyanate-terminated prepolymers contains the constituent unit derived from PTMG, and the isocyanate-terminated prepolymer containing the constituent unit derived from PTMG has an NCO equivalent of 400 or more and 500 or less.

[0036]

[17] According to the abrasive pad of

[13] , wherein the polyurethane resin foam uses at least two isocyanate-terminated prepolymers as raw materials, at least one of the at least two isocyanate-terminated prepolymers contains the constituent unit derived from polyester glycol, and the isocyanate-terminated prepolymer containing the constituent unit derived from polyester glycol has an NCO equivalent of 550 or more and 700 or less.

[0037] The effects of the invention

[0038] It is believed that when the ratio of crystalline phase to amorphous phase in the polishing layer, as determined by pulse NMR in a wet state, is adjusted to a specific range, the proportion of highly mobile amorphous phase is greater than that of crystalline or intermediate phases. The polishing layer softens moderately during polishing, thus becoming a polishing pad with excellent step elimination and planarization performance even in the polished material where step differences of different heights are mixed.

[0039] Furthermore, it is believed that when transitioning from a dry to a wet state, the change in the proportion of the intermediate phase in the abrasive layer is small, and the proportion of the amorphous phase in the abrasive layer is greater than that of the crystalline or intermediate phase, resulting in moderate softening of the abrasive layer during abrasion. Abrasive pads incorporating this type of abrasive layer exhibit excellent step elimination and planarization performance in workpieces with varying step heights. Attached Figure Description

[0040] [ Figure 1 ] Figure 1 This is a schematic diagram illustrating the grinding process.

[0041] [ Figure 2 ] Figure 2 This is a cross-sectional view of the abrasive pad.

[0042] [ Figure 3 ] Figure 3 This is a schematic diagram used to illustrate the performance of step elimination and flattening. Detailed Implementation

[0043] The following describes the forms used to implement the invention, but the invention is not limited to the forms used to implement the invention.

[0044] <<Abrasive Pad>>

[0045] use Figure 2 Explain the structure of abrasive pad 3. For example... Figure 2 Thus, the abrasive pad 3 includes an abrasive layer 4 and a buffer layer 6. The shape of the abrasive pad 3 is preferably disc-shaped, but there is no particular limitation. In addition, the size (diameter) can be appropriately determined according to the size of the abrasive device 1 including the abrasive pad 3, for example, it can be set to a diameter of about 10 cm to 2 m.

[0046] Furthermore, the abrasive pad 3 of the present invention is preferably as follows: Figure 2 As shown, the polishing layer 4 is attached to the buffer layer 6 via the bonding layer 7.

[0047] The abrasive pad 3 is attached to the abrasive pressure plate 10 of the abrasive device 1 via double-sided adhesive tape or similar material disposed on the buffer layer 6. The abrasive pad 3 is driven to rotate by the abrasive device 1 while pressing the workpiece 8, thereby abrading the workpiece 8.

[0048] <Abrasive Layer>

[0049] (structure)

[0050] The abrasive pad 3 includes an abrasive layer 4, which serves as a layer for abrading the workpiece 8. The abrasive layer 4 is made of polyurethane foam. The material and manufacturing method of the polyurethane foam will be described later.

[0051] The size (diameter) of the abrasive layer 4 is the same as that of the abrasive pad 3, which can be set to a diameter of about 10 cm to 2 m, and the thickness of the abrasive layer 4 can be set to about 0.8 mm to 5 mm.

[0052] The grinding layer 4 rotates together with the grinding pressure plate 10 of the grinding device 1. While the slurry 9 flows on it, the chemical components or grinding particles contained in the slurry 9 move relative to the workpiece 8 being ground, thereby grinding the workpiece 8.

[0053] Hollow microspheres 4A (foamed) may be dispersed in the grinding layer 4, or they may not be present. Preferably, hollow microspheres 4A are dispersed in the grinding layer 4.

[0054] (groove machining)

[0055] Preferably, grooves are formed on the surface of the grinding layer 4 on the side of the workpiece 8, as needed. The grooves are not particularly limited and can be either a slurry discharge groove communicating with the periphery of the grinding layer 4 or a slurry holding groove not communicating with the periphery of the grinding layer 4. Alternatively, both a slurry discharge groove and a slurry holding groove may be present. Examples of slurry discharge grooves include grid-shaped grooves and radial grooves; examples of slurry holding grooves include concentric circular grooves and perforations (through holes), and combinations of these may also be used.

[0056] (Shaw D hardness)

[0057] The Shore D hardness of the abrasive layer 4 of the present invention is not particularly limited, but is, for example, 20 or more and 100 or less, preferably 30 or more and 80 or less, and more preferably 40 or more and 70 or less. When the Shore D hardness is low, it is difficult to smooth out fine irregularities through low-pressure grinding. If the Shore D hardness is too high, there is a possibility that the workpiece 8 will be subjected to strong friction, resulting in scratches on the processed surface of the workpiece 8.

[0058] (density)

[0059] The density of the polishing layer 4 in this invention is not particularly limited, for example, it is 0.60 g / cm³. 3 Above and 1.25 g / cm 3 The preferred value is 0.65 g / cm³. 3 Above and 1.15 g / cm3 If the density of the polishing layer 4 is within the specified range, there is a tendency to maintain the hardness of the polishing layer 4 and achieve good step elimination performance.

[0060] In the abrasive pad 3 of the present invention, when hollow microspheres 4A are used, air bubbles are encapsulated within the polyurethane resin molded body due to the hollow microspheres 4A. A hollow microsphere refers to a microsphere having pores. The shape of the hollow microspheres 4A includes spherical, elliptical, and shapes similar to these. Examples include expanded materials and materials formed by heating and expanding unexpanded thermoplastic microspheres.

[0061] (Regarding step elimination performance and flattening performance)

[0062] The abrasive pad of the present invention is characterized by having excellent step elimination and planarization performance by having a specific abrasive layer.

[0063] The abrasive pad 3 of the present invention has excellent step elimination performance.

[0064] Here, the term "step reduction performance" refers to the ability to reduce the step difference (unevenness) of a patterned wafer with step differences (unevenness) during polishing. A schematic diagram of the experiment used to measure the step reduction performance is shown below. Figure 3 In. Figure 3 At time point (a), there are different height differences in the material being polished 8. Polishing is performed using a polishing pad with high step difference elimination performance, prioritizing the polishing of the patterned wafer's step differences and quickly polishing it to the same height as the unwired portion, thus eliminating the step differences. Figure 3 (b)). On the other hand, polishing pads that take a long time to eliminate the step difference of the patterned wafer are polishing pads with low step difference elimination performance.

[0065] Furthermore, the present invention aims to improve the step elimination performance and flattening performance when grinding a workpiece with mixed steps of different heights.

[0066] use Figure 3 To illustrate more specifically, for example, the workpiece being polished consists of a substrate and a metal film thereon, and the metal film is polished using the polishing pad of the present invention. If one example is given, it would be as follows... Figure 3 Thus, the workpiece 8 is composed of a substrate 81 and a metal film 82 formed on the substrate (in addition, Figure 3 (This is a cross-sectional view of the material being ground, 8). Before grinding, as... Figure 3As in (a), the formed metal film 82 has the following characteristics: In the metal film formed directly above the unwired portion 811 of the substrate 81, the metal film formed from the surface (highest position) 813 of the substrate 81 has a small thickness; on the other hand, in the metal films formed directly above the wired portions 812 and 813 of the substrate 81, the metal film formed from the surface of the substrate 81 has a large thickness, resulting in steps (82A, 82B). Furthermore, if the width of the wire becomes narrower, the thickness of the metal film increases. That is, the height of the step 82B directly above the wire 813 with a small wire width is X, while the height of the step 82A directly above the wire 812 with a large wire width is Y, and X is greater than Y.

[0067] When grinding the workpiece 8 in this manner, if the grinding is performed using a grinding pad with excellent step elimination and planarization properties, then as follows: Figure 3 As in (b), the wiring portion 812 is preferentially ground on the surface of the metal film 82 of the workpiece 8, thereby eliminating the step difference and making it flat regardless of the positions of the unwired portion 811, the wiring portion 812, and the wiring portion 813. Thereafter, the metal film 82 of the workpiece 8 is ground in a flat state.

[0068] On the other hand, if polishing is performed using a polishing pad that lacks step elimination performance, it will take time until the thickness of the metal film directly above the wiring portion 812 and wiring portion 813 becomes equal to the thickness of the metal film in the unwired portion 811. If polishing is performed using a polishing pad that lacks planarization performance, not only the metal film directly above the wiring portion will be polished, but the metal film will not become flat when polishing is carried out in other parts.

[0069] Furthermore, step elimination performance represents the degree of flattening of the step differences (unevenness) in a patterned wafer that has undergone grinding. Specifically, the patterned wafer with unevenness is ground, and the residual step differences (the degree of flattening of the step difference portion) of the wafer after grinding are evaluated. Additionally, flattening performance evaluates whether the step difference between the metal film in the unwired portion and the metal film in the wired portion disappears and becomes flat after grinding.

[0070] (Crystalline phase, mesophase, amorphous phase)

[0071] The proportions of the crystalline, mesophase, and amorphous phases in the polished layer were determined using pulsed NMR. In pulsed NMR, the free induction decay (FID) signal was subtracted sequentially from the component with the longest spin-spin relaxation time using the least squares method, resulting in three components. More specifically, the initial value of the obtained FID signal is proportional to the number of protons in the sample. When three components are present in the sample, the FID signal appears as the sum of the response signals of the three components. On the other hand, due to differences in the mobility of the components in the sample, the decay rates of the response signals and the spin-spin relaxation times differ between components. Therefore, the least squares method can be used to classify the polyurethane resin foam into three phases—short phase (S phase), medium phase (M phase), and long phase (L phase)—according to the order of shortest to longest spin-spin relaxation time, and the proportion of each phase is determined. Furthermore, regarding the proportions of the S, M, and L phases, for example, when the main component is a crystalline phase, it is observed as the S phase in pulsed NMR measurements; when the main component is an amorphous phase, it is observed as the L phase; and when the main component is an intermediate phase, it is observed as the M phase. Additionally, when the main component is a hard segment, it is observed as the S phase in pulsed NMR measurements, and when the main component is a soft segment, it is observed as the L phase.

[0072] Furthermore, the spin-spin relaxation time can be determined, for example, by measurement using the solid echo method performed by the "JNM-MU25" manufactured by JEOL.

[0073] During the grinding process, the grinding pad temperature reaches 40°C. If the grinding pad becomes excessively hard due to an increased proportion of hard segments during grinding, scratches are easily generated, and the defect performance may decrease. On the other hand, if the grinding pad softens due to an increased proportion of soft segments, the step elimination and planarization performance deteriorates, which is undesirable. Here, in the crystalline phase, the component with low mobility corresponds to the hard segment component, and in the amorphous phase, the component with high mobility corresponds to the soft segment component. The ratio of hard segment components to soft segment components affects the hardness and other physical properties of the grinding pad.

[0074] Furthermore, pulse NMR measurements were previously performed under dry conditions. However, as mentioned above, actual grinding is carried out while supplying a slurry containing a mixture of water and various chemical components or hard, finely abrasive particles. Although actual experimental results are described in the examples, it has been determined that the results of pulse NMR measurements performed under dry conditions differ from those performed under humid conditions.

[0075] Furthermore, in this specification, the so-called measurement by pulse NMR in a wet state refers to immersing the material of the polishing layer in pure water for 24 hours, wiping the surface of the polishing layer with pure water using a Kimtowel (registered trademark), and performing pulse NMR measurement at a specified temperature (40°C in this invention).

[0076] In the polishing layer of the first-type polishing pad, the ratio of the crystalline phase to the amorphous phase in the polishing layer, measured by pulsed NMR at 40°C in a wet state, is 0.5 or more and 1.0 or less. The ratio of the crystalline phase to the amorphous phase is preferably 0.55 or more and 0.95 or less, more preferably 0.60 or more and 0.90 or less, and even more preferably 0.55 or more and 0.85 or less. Furthermore, the ratio of the intermediate phase to the amorphous phase in the polishing layer, measured by pulsed NMR at 40°C in a wet state, is 0.4 or more and 0.9 or less. The ratio of the intermediate phase to the amorphous phase is preferably 0.45 or more and 0.85 or less, more preferably 0.50 or more and 0.80 or less.

[0077] By measuring the ratio of crystalline phase to amorphous phase and the ratio of intermediate phase to amorphous phase in the polishing layer under wet conditions at 40°C using pulsed NMR, respectively, within the specified ranges, the proportion of highly mobile amorphous phase is greater than that of crystalline or intermediate phases during polishing. This results in the polishing layer softening appropriately during polishing, thereby obtaining a polishing pad with excellent step elimination and planarization performance.

[0078] In the polishing layer of the first-type polishing pad, the content of the amorphous phase in the polishing layer, as measured by pulse NMR at 40°C in a wet state, is preferably 30.0% or more and 55.0% or less, more preferably 32.0% or more and 50.0% or less, and even more preferably 35.0% or more and 50.0% or less. By satisfying the above range, the proportion of the highly mobile amorphous phase is moderately present, and the polishing layer softens moderately during polishing, thereby tending to have excellent step elimination performance and planarization performance.

[0079] In the abrasive layer of the first-type abrasive pad, the proportion of the intermediate phase in the abrasive layer, as measured by pulse NMR at 40°C in a wet state, is preferably 15.0% or more and 35.0% or less, more preferably 17.0% or more and 33.0% or less, and even more preferably 20.0% or more and 30.0% or more.

[0080] In the polishing layer of the first-type polishing pad, the content of the crystalline phase in the polishing layer, as measured by pulse NMR at 40°C in a wet state, is 25.0% or more and 45.0% or less, preferably 28.0% or more and 42.0% or less, and more preferably 28.0% or more and 35.0% or less. By satisfying the above range, the proportion of the crystalline phase with low mobility is moderately present, and the polishing layer has moderate hardness during polishing, thereby tending to have excellent step elimination performance and planarization performance.

[0081] As another embodiment, in the abrasive layer of the abrasive pad of the present invention, the value obtained by subtracting the content of the intermediate phase of the abrasive layer in the dry state, as measured by pulse NMR at 40°C, from the content of the intermediate phase of the abrasive layer in the wet state, is -2.0% or more and 2.0% or less, preferably -1.5% or more and 1.8% or less, and more preferably -0.9% or more and 1.5% or less.

[0082] Furthermore, the value obtained by subtracting the amorphous phase content of the polishing layer measured by pulse NMR at 40°C in the dry state from the amorphous phase content of the polishing layer in the wet state is 2.0% or more and 5.7% or less, preferably 2.5% or more and 5.6% or less, more preferably 3.0% or more and 5.6% or less, and even more preferably 4.0% or more and 5.5% or less.

[0083] The values ​​obtained by subtracting the proportion of the intermediate phase in the polishing layer measured by pulsed NMR at 40°C in the dry state from the proportion of the intermediate phase in the polishing layer measured by pulsed NMR at 40°C in the wet state, and the values ​​obtained by subtracting the proportion of the amorphous phase in the polishing layer measured by pulsed NMR at 40°C in the dry state from the proportion of the amorphous phase in the polishing layer measured by pulsed NMR at 40°C in the wet state, respectively satisfy the aforementioned ranges. As a result, when transitioning from a dry state to a wet state, the change in the proportion of the intermediate phase in the polishing layer is small, the proportion of the highly mobile amorphous phase increases moderately, and the polishing layer softens moderately during polishing, thereby exhibiting excellent step elimination and planarization performance.

[0084] In the polishing layer of the second type of polishing pad, preferably, the proportion of crystalline phase in the polishing layer, measured by pulse NMR at 40°C in a wet state, is smaller than the proportion of amorphous phase. By satisfying this range, the proportion of highly mobile amorphous phase is larger than the proportion of less mobile crystalline phase, and the polishing layer softens moderately during polishing, thereby exhibiting excellent step elimination and planarization performance.

[0085] In the polishing layer of the second type of polishing pad, the content of the amorphous phase in the polishing layer, as measured by pulse NMR at 40°C in a wet state, is preferably 30.0% or more and 55.0% or less, more preferably 32.0% or more and 50.0% or less, and even more preferably 35.0% or more and 50.0% or less. By satisfying the above range, the proportion of the highly mobile amorphous phase is moderately present, and the polishing layer softens moderately during polishing, thereby tending to have excellent step elimination performance and planarization performance.

[0086] Furthermore, in the abrasive layer of the second type of abrasive pad, the content of the amorphous phase in the abrasive layer, as measured by pulse NMR at 40°C in the dry state, is preferably 30.0% or more and 50.0% or less, more preferably 32.0% or more and 48.0% or less, and even more preferably 34.0% or more and 45.0% or less. By satisfying the above range, the proportion of the amorphous phase in the wet state can be easily adjusted.

[0087] In the second type of polishing layer, the content of the intermediate phase in the polishing layer in the wet state, as measured by pulse NMR at 40°C, is preferably 15.0% or more and 35.0% or less, more preferably 17.0% or more and 33.0% or less, and even more preferably 20.0% or more and 30.0% or less.

[0088] In the polishing layer of the second type of polishing pad, the content of the crystalline phase in the polishing layer, as measured by pulse NMR at 40°C in a wet state, is 25.0% or more and 45.0% or less, preferably 28.0% or more and 42.0% or less, and more preferably 28.0% or more and 35.0% or less. By satisfying the above range, the proportion of the crystalline phase with low mobility is moderately present, and the polishing layer has moderate hardness during polishing, thereby tending to have excellent step elimination performance and planarization performance.

[0089] <Buffer Layer>

[0090] (structure)

[0091] The abrasive pad 3 of the present invention has a buffer layer 6. The buffer layer 6 ideally ensures more uniform contact between the abrasive layer 4 and the workpiece 8. Examples of materials for the buffer layer 6 include: resin; impregnated materials formed by impregnating a substrate with resin; flexible materials such as synthetic resins or rubber; and sponge materials using resin. Examples of resins include: polyurethane, polyethylene, polybutadiene, silicone, etc., or rubbers such as natural rubber, nitrile rubber, and polyurethane rubber.

[0092] The buffer layer 6 can also be a foam with a bubble structure. As a bubble structure, in addition to a structure with pores formed inside the nonwoven fabric, a suede-like structure with teardrop-shaped bubbles formed by wet film formation or a sponge-like structure with microbubbles can preferably be used.

[0093] Among these, if a material made by impregnating polyurethane in nonwoven fabric or a sponge-like material is used as a buffer layer, it has good compatibility with the abrasive layer and can therefore maintain excellent step elimination performance.

[0094] <Next layer>

[0095] The adhesive layer 7 is used to bond the buffer layer 6 to the abrasive layer 4, and typically comprises double-sided tape or adhesive. Double-sided tape or adhesive may be those known in the art (e.g., adhesive sheets).

[0096] The abrasive layer 4 and the buffer layer 6 are bonded together by the adhesive layer 7. The adhesive layer 7 may be formed, for example, by at least one adhesive selected from acrylic, epoxy, and urethane adhesives. For example, an acrylic adhesive may be used, and the thickness may be set to 0.1 mm.

[0097] <<Manufacturing Method of Grinding Pads>>

[0098] The manufacturing method of the abrasive pad 3 of the present invention will be described.

[0099] <Materials of the Abrasive Layer>

[0100] Polyurethane resin foam is used as the material for the abrasive layer 4. Examples of materials that can be used as the main component include those obtained by reacting isocyanate-terminated prepolymers with a curing agent. Furthermore, a foaming agent is added to the material to induce foaming.

[0101] The following describes the manufacturing method of the polishing layer 4 using an example of an isocyanate-terminated prepolymer and a hardener.

[0102] As a method for manufacturing the polishing layer 4 using isocyanate-terminated prepolymer and hardener, for example, the manufacturing method includes: a material preparation step, which prepares at least an isocyanate-terminated prepolymer and a hardener; a mixing step, which mixes at least the isocyanate-terminated prepolymer and the hardener to obtain a molding mixture; and a molding step, which shapes the polishing layer 4 from the molding mixture.

[0103] The following steps are divided into material preparation, mixing, and forming steps, which will be explained separately.

[0104] <Materials Preparation Steps>

[0105] To manufacture the abrasive layer 4 of the present invention, isocyanate-terminated prepolymer, a hardener, and hollow microspheres are prepared as raw materials for the polyurethane resin foam. Here, the isocyanate-terminated prepolymer is a urethane prepolymer (sometimes simply referred to as prepolymer) used to form the polyurethane resin foam.

[0106] The following is a description of each component.

[0107] (Isocyanate-terminated prepolymer)

[0108] The isocyanate-terminated prepolymer may contain building blocks derived from polyisocyanate compounds and building blocks derived from polyols. It is a compound obtained by reacting the polyisocyanate compound with a polyol under normally used conditions, and contains urethane bonds and isocyanate groups within the molecule. Furthermore, other components may be included in the isocyanate-terminated prepolymer without impairing the effects of the invention. From the viewpoint of property adjustment and operation, two or more different types of isocyanate-terminated prepolymers may be used.

[0109] As isocyanate-terminated prepolymers, commercially available alternatives can be used, as well as those synthesized by reacting polyisocyanate compounds with polyols. There are no particular limitations on the reaction; any addition polymerization reaction using methods and conditions known in the manufacture of polyurethane resins can be employed. For example, it can be manufactured by adding a polyisocyanate compound heated to 50°C to a polyol heated to 40°C under nitrogen atmosphere with stirring, followed by raising the temperature to 80°C after 30 minutes and reacting at 80°C for 60 minutes.

[0110] (Polyisocyanate compounds)

[0111] In this specification, the term "polyisocyanate compound" refers to a compound having two or more isocyanate groups within its molecule.

[0112] As polyisocyanate compounds, there are no particular restrictions as long as they have two or more isocyanate groups within the molecule. Examples of diisocyanate compounds with two isocyanate groups within the molecule include: isophenylene diisocyanate, terephthalene diisocyanate, 2,6-tolylene diisocyanate (2,6-TDI), 2,4-tolylene diisocyanate (2,4-TDI), naphthalene-1,4-diisocyanate, diphenylmethane-4,4'-diisocyanate (MDI), 4,4'-methylene-bis(cyclohexyl)isocyanate (hydrogenated MDI), 3,3'-dimethoxy-4,4'-biphenyl diisocyanate, 3,3 Polyisocyanates include '-dimethyldiphenylmethane-4,4'-diisocyanate, xylene-1,4-diisocyanate, 4,4'-diphenylpropane diisocyanate, trimethylene diisocyanate, hexamethylene diisocyanate, propylene-1,2-diisocyanate, butylene-1,2-diisocyanate, cyclohexylene-1,2-diisocyanate, cyclohexylene-1,4-diisocyanate, terephthalene diisothiocyanate, xylene-1,4-diisothiocyanate, and ethylene diisothiocyanate. These polyisocyanate compounds can be used alone or in combination.

[0113] Furthermore, as a polyisocyanate compound, it is preferred to contain 2,4-TDI and / or 2,6-TDI, and more preferably 2,4-TDI.

[0114] (Polyols as raw materials for prepolymers)

[0115] In this specification, the term "high molecular weight polyol" refers to a compound having two or more hydroxyl groups (OH) within its molecule, and "high molecular weight" refers to a molecular weight of 500 or higher.

[0116] The polyol compounds used as raw materials for prepolymers are not particularly limited as long as they can achieve the purpose of this invention. Examples include: diol compounds such as ethylene glycol, diethylene glycol (DEG), and butanediol; triol compounds such as poly(oxytetramethylene) glycol (or polytetramethylene ether glycol) (PTMG), polypropylene glycol (PPG), polyether polycarbonate diol (PEPCD), and polyester polyols.

[0117] In the first embodiment, the polishing layer, in order to satisfy the requirement that the ratio of the crystalline phase to the amorphous phase in the polishing layer, as measured by pulse NMR at 40°C in the wet state, is 0.5 or more and 1.0 or less, and the ratio of the intermediate phase to the amorphous phase in the polishing layer, as measured by pulse NMR at 40°C in the wet state, is 0.4 or more and 0.9 or less, preferably comprises a high molecular weight polyol-derived unit comprising a unit derived from polyoxytetramethylene glycol (PTMG) and a unit derived from polyester glycol. As a preferred embodiment, other polyol components may be used besides PTMG and polyester glycol.

[0118] In the second embodiment, the composition of the abrasive layer preferably contains at least a value of -2.0% to 2.0% (obtained by subtracting the proportion of the intermediate phase of the abrasive layer in the dry state from the proportion of the intermediate phase in the wet state measured by pulsed NMR at 40°C) and a value of 2.0% to 5.7% (obtained by subtracting the proportion of the amorphous phase in the wet state measured by pulsed NMR at 40°C) from the proportion of the amorphous phase in the dry state measured by pulsed NMR at 40°C). The constituent units derived from high molecular weight polyols preferably include at least a constituent unit derived from polyoxytetramethylene glycol (PTMG) and a constituent unit derived from polyester glycol. As a preferred embodiment, other polyol components besides PTMG and polyester glycol may also be used.

[0119] When using a combination of polyoxytetramethylene glycol (PTMG) and polyester glycol, the weight percentage of PTMG relative to the total weight of the high molecular weight polyol compound used as the prepolymer raw material is preferably 30% by weight or more and 80% by weight or less.

[0120] The polyester diol is not particularly limited as long as it is a synthesis of an acid and a diol, and examples include: oxalic acid, malonic acid, succinic acid, glutaric acid, adipic acid, pimelic acid, octanoic acid, azelaic acid, sebacic acid, phthalic acid, isophthalic acid, terephthalic acid, etc. Additionally, examples of diols used in the polyester diol include: ethylene glycol, diethylene glycol (DEG), butanediol (1,4-butanediol), neopentyl glycol, 1,3-butanediol, 1,5-pentanediol, 1,6-hexanediol, etc. Among the compounds, a polyester diol synthesized from adipic acid and 1,4-butanediol, in a proportion that allows for easy adjustment of the crystalline and amorphous phase ratio, is preferred.

[0121] The number average molecular weight (Mn) of the polyester glycol used to form the constituent units derived from polyester glycol is preferably 600 or more and 2500 or less, more preferably 800 or more and 2000 or less. Here, the number average molecular weight can be determined by gel permeation chromatography (GPC). Furthermore, when determining the number average molecular weight of the polyol compound based on polyurethane resin, it can also be inferred by GPC after decomposing each component using conventional methods such as amine decomposition. With a number average molecular weight of 600 to 2500, the abrasive pad can be given the desired rubber elasticity, and there is a tendency to obtain the effects of the present invention.

[0122] (NCO equivalent of isocyanate-terminated prepolymer)

[0123] When using two or more isocyanate-terminated prepolymers, the NCO equivalent of the isocyanate-terminated prepolymers is preferably 400 or more and 500 or less, more preferably 420 or more and 490 or less, in isocyanate-terminated prepolymers containing constituent units derived from PTMG; and preferably 550 or more and 700 or less, more preferably 570 or more and 660 or less, in isocyanate-terminated prepolymers forming constituent units derived from polyester glycol. Furthermore, when using two or more isocyanate-terminated prepolymers, the NCO equivalent of the mixed isocyanate-terminated prepolymer is preferably 400 or more and 650 or less, more preferably 410 or more and 570 or less. By satisfying these ranges, there is a tendency to obtain excellent step elimination performance and flattening performance.

[0124] Therefore, when the isocyanate-terminated prepolymer is a commercially available product, it is preferable that the NCO equivalent meets the range described above. When manufactured by synthesis, it is preferable that the NCO equivalent within the range is achieved by using the following raw materials in a suitable proportion.

[0125] (additive)

[0126] As described above, additives such as oxidants can be added as needed to the material of the polishing layer 4.

[0127] (hardener)

[0128] In the manufacturing method of the polishing layer 4 of the present invention, a hardener (also called a chain elongating agent) is mixed with an isocyanate-terminated prepolymer in a mixing step. By adding the hardener, in a subsequent molding step, the main chain ends of the isocyanate-terminated prepolymer are bonded to the hardener to form a polymer chain, and the mixture is then hardened.

[0129] Examples of hardening agents include: ethylenediamine, propylenediamine, hexamethylenediamine, isophoronediamine, dicyclohexylmethane-4,4'-diamine, 3,3'-dichloro-4,4'-diaminodiphenylmethane (MOCA), 4-methyl-2,6-bis(methylthio)-1,3-phenylenediamine, 2-methyl-4,6-bis(methylthio)-1,3-phenylenediamine, and 2,2-bis(3-amino-4-hydroxyphenyl)propane. 2,2-bis[3-(isopropylamino)-4-hydroxyphenyl]propane, 2,2-bis[3-(1-methylpropylamino)-4-hydroxyphenyl]propane, 2,2-bis[3-(1-methylpentylamino)-4-hydroxyphenyl]propane, 2,2-bis(3,5-diamino-4-hydroxyphenyl)propane, 2,6-diamino-4-methylphenol, trimethyl ethylidene bis-4-aminobenzoate, and polytetramethylene Polyamine compounds such as di-p-aminobenzoate; ethylene glycol, propylene glycol, diethylene glycol, trimethylene glycol, tetraethylene glycol, triethylene glycol, dipropylene glycol, 1,4-butanediol, 1,3-butanediol, 2,3-butanediol, 1,2-butanediol, 3-methyl-1,2-butanediol, 1,2-pentanediol, 1,4-pentanediol, 2,4-pentanediol, 2,3-dimethyltrimethylenediol, and tetramethylenediol. Polyols such as 3-methyl-4,3-pentanediol, 3-methyl-4,5-pentanediol, 2,2,4-trimethyl-1,3-pentanediol, 1,6-hexanediol, 1,5-hexanediol, 1,4-hexanediol, 2,5-hexanediol, 1,4-cyclohexanediol, neopentanediol, glycerol, trimethylolpropane, trimethylolethane, trimethylolmethane, poly(oxytetramethylene) glycol, polyethylene glycol, and polypropylene glycol are included. Additionally, polyamine compounds may possess hydroxyl groups. Examples of such amine compounds include 2-hydroxyethylethylenediamine, 2-hydroxyethylpropanediamine, di-2-hydroxyethylethylenediamine, di-2-hydroxyethylpropanediamine, 2-hydroxypropylethylenediamine, and di-2-hydroxypropylethylenediamine. As a polyamine compound, a diamine compound is preferred, and more preferably, 3,3'-dichloro-4,4'-diaminodiphenylmethane (methylene bis-o-chloroaniline) (hereinafter referred to as MOCA) is used.

[0130] Furthermore, as a raw material for isocyanate-terminated prepolymers, when using two or more high molecular weight polyols, a raw material obtained by mixing two or more high molecular weight polyols and reacting the polyisocyanate compound with the mixture can be used, or a method of reacting two or more high molecular weight polyols separately with the polyisocyanate compound, mixing them, and then hardening them can be used.

[0131] (Hollow microspheres)

[0132] The abrasive layer 4 can be formed by using hollow microspheres 4A with a shell and a hollow interior in the material. Commercially available materials or materials synthesized using conventional methods can be used as the material for the hollow microspheres 4A. There are no particular limitations on the material of the shell of the hollow microspheres 4A; examples include: polyvinyl alcohol, polyvinylpyrrolidone, poly(meth)acrylic acid, polyacrylamide, polyethylene glycol, polyhydroxy ether acrylate, maleic acid copolymer, polyethylene oxide, polyurethane, poly(meth)acrylonitrile, polyvinylidene chloride, polyvinyl chloride, and silicone resins, as well as copolymers combining two or more monomers of these resins (e.g., acrylonitrile-vinylidene chloride copolymer, etc.). In addition, commercially available hollow microspheres are not limited to the following, for example, the Expancel Series (a trade name manufactured by Japan Fillite Co., Ltd.) and the Matsumoto Microsphere (a trade name manufactured by Matsumoto Oils, Ltd.) are examples.

[0133] The gas contained in the hollow microsphere 4A is not particularly limited; for example, hydrocarbons can be listed, specifically isobutane, pentane, isopentane, etc.

[0134] The shape of the hollow microspheres 4A is not particularly limited; for example, they can be spherical or approximately spherical. The average particle size of the hollow microspheres 4A is not particularly limited, but is preferably 5 μm to 200 μm, more preferably 5 μm to 80 μm, even more preferably 5 μm to 50 μm, and particularly preferably 5 μm to 35 μm. Furthermore, the average particle size can be measured using a laser diffraction particle size distribution measuring device (e.g., Spectris Mastersizer-2000 particle size analyzer).

[0135] The material of the hollow microspheres 4A is added in a manner that is preferably 0.1 to 10 parts by mass, more preferably 1 to 5 parts by mass, and even more preferably 1 to 4 parts by mass relative to 100 parts by mass of the isocyanate-terminated prepolymer.

[0136] In addition to the aforementioned components, the previously used foaming agent may be used in combination with the hollow microspheres 4A without impairing the effects of the present invention, and a gas that is non-reactive to each component may be blown in during the following mixing steps. As the foaming agent, in addition to water, foaming agents with hydrocarbons having 5 or 6 carbon atoms as the main component may be listed. Examples of such hydrocarbons include chain hydrocarbons such as n-pentane and n-hexane, or alicyclic hydrocarbons such as cyclopentane and cyclohexane.

[0137] <Mixing Steps>

[0138] In the mixing step, the isocyanate-terminated prepolymer, additives, and hardener obtained in the preparation step are fed into a mixer for stirring and mixing. The mixing step is carried out at a temperature that ensures the flowability of the components.

[0139] <Forming Steps>

[0140] In the molding step, the molding mixture prepared in the mixing step is poured into a mold frame preheated to 60°C–120°C, and hardened once at 100°C–150°C for 30 minutes to 1 hour. Afterward, the hardened molded body is removed from the mold frame and heated at approximately 100°C–150°C for approximately 2 hours to 6 hours for a second hardening, thereby molding the hardened polyurethane resin (polyurethane resin foam). At this time, the urethane prepolymer and hardener react to form polyurethane resin, thus hardening the mixture.

[0141] If the viscosity of the urethane prepolymer (isocyanate-terminated prepolymer) is too high, its flowability deteriorates, making it difficult to mix approximately uniformly during mixing. If the viscosity is decreased by increasing the temperature, the pot life is shortened, resulting in uneven mixing and variations in the size of the hollow microspheres 4A formed in the resulting foam. Conversely, if the viscosity is too low, air bubbles will move in the mixture, making it difficult to form hollow microspheres 4A that are dispersed approximately evenly in the resulting foam. Therefore, the urethane prepolymer is preferably set to a viscosity in the range of 500 mPa·s to 10000 mPa·s at a temperature of 50°C to 80°C. In this case, the viscosity can be set, for example, by changing the molecular weight (degree of polymerization) of the urethane prepolymer. The urethane prepolymer is heated to approximately 50°C to 80°C to achieve a flowable state.

[0142] In the molding step, the poured mixture is reacted within a mold as needed to form a polyurethane resin foam. At this point, cross-linking and curing occur through the reaction of the urethane prepolymer with a hardener.

[0143] After obtaining the polyurethane resin foam, it is sliced ​​into sheets to form multiple polished layers 4. A general-purpose slicer can be used for slicing. During slicing, the lower portion of the polished layer 4 is held in place, and slices are made sequentially from the upper portion to a predetermined thickness. The slice thickness is set, for example, within the range of 0.8 mm to 2.5 mm. In a polyurethane resin foam formed using a mold with a thickness of 50 mm, approximately 10 mm of the upper and lower portions of the polyurethane resin foam are not used due to scratches or other defects, and 10 to 25 polished layers 4 are formed from the approximately 30 mm portion in the center. This yields a polyurethane resin foam in which hollow microspheres 4A are formed approximately evenly inside.

[0144] Grooving is performed on the grinding surface of the obtained grinding layer 4 as needed. Grooves with arbitrary spacing, width, and depth can be formed by cutting the grinding surface using a required tool. For example, circular grooves formed in a concentric circle shape can be used as slurry holding grooves, and linear grooves formed in a grid shape or linear grooves formed radially from the center of the grinding layer can be used as slurry discharge grooves.

[0145] Regarding the polishing layer 4 obtained in this way, double-sided tape is then applied to the side of the polishing layer 4 opposite to the polishing surface. There are no particular limitations on the double-sided tape, and any double-sided tape known in this art can be selected and used.

[0146] <Manufacturing Method of Buffer Layer 6>

[0147] As described above, examples of materials that can be used as the buffer layer 6 include: impregnated materials made by impregnating a resin solution such as urethane in resin fibers (non-woven fabrics, flexible films, etc.) such as polyethylene or polyester; suede-like materials using resin materials such as urethane; and sponge materials using materials such as urethane. In this invention, the buffer layer 6 can utilize known materials, and the manufacturing method can also use known methods.

[0148] <Jointing Steps>

[0149] In the bonding step, the formed abrasive layer 4 and buffer layer 6 are bonded together using adhesive layer 7. Adhesive layer 7 is formed, for example, using an acrylic adhesive, with a thickness of 0.1 mm. That is, an acrylic adhesive is applied to the side of abrasive layer 4 opposite to the abrasive surface with a substantially uniform thickness. The side of abrasive layer 4 opposite to the abrasive surface P and the surface of buffer layer 6 (the side with the surface layer) are pressed together using the applied adhesive, thereby bonding abrasive layer 4 and buffer layer 6 together using adhesive layer 7. Then, after being cut into the desired shape such as a circle, an inspection is performed to confirm the absence of dirt or foreign matter, thereby completing abrasive pad 3.

[0150] Example

[0151] The present invention will now be described in more detail by way of examples, but the present invention is not limited to these examples.

[0152] In all embodiments and comparative examples, unless otherwise specified, the term "parts" refers to "parts by mass".

[0153] In addition, the so-called NCO equivalent is the molecular weight of the prepolymer (PP) with each NCO group, calculated using "(mass (parts) of polyisocyanate compound + mass (parts) of polyol)) / [(number of functional groups per molecule of polyisocyanate compound × mass (parts) of polyisocyanate compound / molecular weight of polyisocyanate compound) - (functional groups per molecule of polyol × mass (parts) of polyol / molecular weight of polyol)]".

[0154] (Regarding the polishing layer)

[0155] Two urethane prepolymers (PP1 and PP2) were prepared by reacting 2,4-toluene diisocyanate (TDI) as an isocyanate compound, PTMG as a polyol compound, with diethylene glycol (DEG) or a polyester polyol (a synthesis of adipic acid and 1,4-butanediol (Adipic acid BG series esters)), and diethylene glycol (DEG) respectively. (The components used in the preparation of the urethane prepolymers are shown in Table 1.) 1.8 parts of hollow microspheres (balloons: Expansel 920DU20 (manufactured by Japan Fillite Co., Ltd.) with an average particle size of 6.0 μm were added to 100 parts of the urethane prepolymer mixture prepared according to the proportions shown in Table 2 to obtain a mixture. The obtained mixture was placed in a first liquid tank and kept at 60°C. Next, independently of the first liquid, 6.2 parts of MOCA2, serving as a hardener, were placed in a second liquid tank, heated to 120°C to melt, and held at that temperature. The liquids from both the first and second liquid tanks were injected into a mixer with two injection ports, each containing an R value of 0.9, representing the equivalent ratio of amino and hydroxyl groups present in the hardener to the terminal isocyanate groups in the prepolymer. The two liquids were mixed and stirred while being poured into a mold preheated to 80°C. The mold was then closed, and the mixture was heated at 80°C for 30 minutes for primary hardening. After demolding the primary hardened product, it was subjected to a secondary hardening in an oven at 120°C for 4 hours to obtain a urethane molded product. After cooling the obtained urethane molded product to 25°C, it was again heated in an oven at 120°C for 5 hours and then cut to a thickness of 1.3 mm to obtain the polished layer B used in Example 1 as shown in Table 2. Polishing layers A, C, D, and E were prepared using the same steps as in Tables 1 and 2. The density and Shore D hardness of each polishing layer are also shown in Table 2, and the proportions of crystalline, mesophase, and amorphous phases are shown in Table 3 (measured at 40°C in both wet and dry states). Furthermore, T(1), T(2), and T(3) in Table 3 represent the relaxation times of the crystalline, mesophase, and amorphous phases, respectively, in milliseconds (msec). Based on this data, specified values ​​are shown in Table 4.

[0156] In addition, the methods and conditions for determining density, Shore D hardness, and pulse NMR (dry and wet states) are as follows.

[0157] (density)

[0158] Density of the grinding layer (g / cm³) 3 The test was conducted in accordance with Japanese Industrial Standards (JIS K 6505).

[0159] (Shore D hardness)

[0160] The Shore D hardness of the abrasive layer was measured using a Shore D type hardness tester according to Japanese Industrial Standard (JIS-K-6253). The test specimens were obtained by overlapping multiple abrasive layers as needed, with a total thickness of at least 4.5 mm.

[0161] (Pulse NMR measurement)

[0162] The device is a Bruker Minispec MQ20 ​​(20 MHz).

[0163] Various 1 H

[0164] Determine T2

[0165] Measurement Method: Solid Echo Method

[0166] Acquisition Scale: 0.4 msec

[0167] 128 scans

[0168] Recycle Delay: 0.5 sec

[0169] Temperature measured at 40℃

[0170] After the device reaches the measurement temperature and the sample is placed, it is allowed to stand for 5 minutes before the measurement begins. A measurement is taken immediately after the measurement begins, followed by measurements every 5 minutes, for a total of 6 measurements. The average value of the second to sixth measurements out of the 6 measurements is taken as the measurement result. For the samples, two types are prepared: a dry sample (8 mm Ø punched from grinding layers A to E and kept in a constant temperature and humidity bath at 23°C (±2°C) and 50% (±5%) for 40 hours), and a wet sample (immersed in pure water for 24 hours, with surface moisture wiped off and measured quickly). The punched samples are filled into the sample tube to a height of 1 cm to 1.5 cm under the aforementioned device and conditions.

[0171] [Table 1]

[0172]

[0173] [Table 2]

[0174]

[0175] [Table 3]

[0176]

[0177] [Table 4]

[0178]

[0179] (Regarding the buffer layer)

[0180] Commercially available sponge-like urethane foam (Shore A hardness 60, density 0.55 g / cm³) was used. 3 (Thickness 1.3mm). The Shore A hardness of the buffer layer was determined according to the Japanese Industrial Standard (JIS-K-7311) based on the depth of the indenter pressed against the surface of the test piece by a spring. Furthermore, the density of the buffer layer was determined in the same manner as that of the abrasive layer.

[0181] (Examples and Comparative Examples)

[0182] Abrasive layers A to E and a buffer layer were bonded together using double-sided tape (containing an adhesive layer containing an acrylic resin on both sides of a polyethylene terephthalate (PET) substrate) with a thickness of 0.1 mm. The double-sided tape was then applied to the side of the buffer layer opposite to the adhesive layer to manufacture abrasive pads of Examples 1 to 3 and Comparative Examples 1 and 2.

[0183] (Grinding performance evaluation)

[0184] Using the abrasive pads obtained in Examples 1 to 3 and Comparative Examples 1 and 2, abrasive tests were conducted under the following abrasive conditions. The results are shown in Table 5.

[0185] (Grinding conditions)

[0186] Grinding machine: F-REX300X (manufactured by Ebara Seisakusho Co., Ltd.)

[0187] Disk: 34R (manufactured by China Grinding Wheel (KINIK) Company)

[0188] Buckle: GXKD buckle (manufactured by Ebara Seisakusho Co., Ltd.)

[0189] Rotation speed: (pressure plate) 90 rpm, (grinding head) 81 rpm

[0190] Grinding pressure: 1.7 psi

[0191] Abrasive temperature: 20℃

[0192] Abrasive spray rate: 200 ml / min

[0193] Abrasive: CSL-9044C (using a mixture of CSL-9044C stock solution and pure water at a weight ratio of 1:9) (manufactured by Fujifilm Planar Solutions).

[0194] Material to be ground: Cu film substrate (disc-shaped, 300 mm in diameter)

[0195] Grinding time: 60 seconds

[0196] Pad break-in: 32 N for 20 minutes

[0197] Conditioning: Ex-situ 32 N 4 scans

[0198] (Performance evaluation test for step elimination)

[0199] The polishing pad is positioned at a predetermined location on the polishing apparatus using double-sided tape with an acrylic adhesive, and polishing is performed under the stated polishing conditions. Regarding step elimination performance, the height of the residual step after polishing patterned wafers (workpieces) with wire widths of 0.18 μm / 0.18 μm and 0.50 μm / 0.50 μm using an atomic force microscope (manufactured by Park Systems) in NC-AFM (non-contact) mode was measured. The thickness of the polished Cu film was measured using a four-probe sheet resistance meter (manufactured by KLA Tencor, trade name "RS-200", measurement: DBS mode). The polishing rate of the Cu film was evaluated based on these measurements.

[0200] More specifically, for the patterned wafer (workpiece) before polishing, the height of the step difference is measured using an atomic force microscope and a four-probe sheet resistance meter. The patterned wafer (workpiece) having a Cu film with a residual height of 10,000 angstroms in the unwired area, a Cu film with a residual height of 21,000 angstroms in the 0.18 μm / 0.18 μm wire width, and a Cu film with a residual height of 14,000 angstroms in the 0.50 μm / 0.50 μm wire width is polished once, and the height of the residual Cu film in each area is measured using an atomic force microscope and a four-probe sheet resistance meter. In Table 5, cases where the difference between the height of the residual step on all wire widths after grinding and the height of the residual step on the ungrinded portion after grinding is less than 1000 angstroms are marked as ○, and cases where the difference between the height of the residual step on all wire widths after grinding and the height of the residual step on the ungrinded portion after grinding is greater than 1000 angstroms are marked as ×.

[0201] (Planarization performance evaluation test)

[0202] The performance degradation caused by planarization is evaluated as follows: for the patterned wafer (the object being polished), the residual height of the unwired areas, 0.18 μm / 0.18 μm areas, and 0.50 μm / 0.50 μm areas after polishing under the specified conditions is measured using an atomic force microscope (AFM) and a four-probe sheet resistance measuring device.

[0203] More specifically, for patterned wafers (the objects to be polished), the residual height of each part after polishing is measured using an atomic force microscope under the aforementioned measurement conditions. In Table 5, those parts where the difference between the maximum and minimum residual height is less than 1000 angstroms are indicated as ○, and those exceeding 1000 angstroms are indicated as ×.

[0204] [Table 5]

[0205]

[0206] According to the results in Table 5, the polishing pads of Examples 1 to 3 have good step elimination and planarization performance because the ratio of crystalline phase to amorphous phase and the ratio of intermediate phase to amorphous phase in the polishing layer, as measured by pulse NMR at 40°C in a wet state, meet the appropriate range.

[0207] Furthermore, according to the results in Table 5, it is known that the polishing pads of Examples 1 to 3 have good step elimination and planarization performance because the values ​​obtained by subtracting the proportion of intermediate phase in the polishing layer measured by pulse NMR at 40°C in the wet state from the proportion of intermediate phase in the polishing layer measured by pulse NMR at 40°C in the dry state, and the values ​​obtained by subtracting the proportion of amorphous phase in the polishing layer measured by pulse NMR at 40°C in the wet state from the proportion of amorphous phase in the polishing layer measured by pulse NMR at 40°C in the dry state, meet the appropriate range.

[0208] In the comparison of varying blending ratios, an improvement in step elimination and planarization performance was observed within the range of approximately 30% to 80% of the PTMG constituent units. It is believed that by applying the strong cohesive force of the ester system, a good balance between hard and soft segments is achieved, resulting in the optimal structure of the grinding layer during grinding. If the grinding layer is too soft, the step elimination and planarization performance deteriorates.

[0209] Industrial availability

[0210] This invention facilitates the manufacture and sale of abrasive pads, and therefore has industrial applicability.

[0211] Explanation of icon numbers

[0212] 1: Grinding device

[0213] 3: Grinding pad

[0214] 4: Grinding layer

[0215] 4A: Hollow microspheres

[0216] 6: Buffer layer

[0217] 7: Next layer

[0218] 8: The material being ground

[0219] 81: Base

[0220] 82: Metal film

[0221] 9: Slurry

[0222] 10: Grinding and pressing plate

Claims

1. An abrasive pad having an abrasive layer comprising a polyurethane resin foam, wherein the polyurethane resin foam uses isocyanate-terminated prepolymer and a curing agent as raw materials, the abrasive pad being characterized in that: The ratio of the crystalline phase content (%) to the amorphous phase content (%) in the polished layer, measured by pulsed nuclear magnetic resonance at 40°C under a wet state, is 0.5 or more and 1.0 or less. The ratio of the percentage of intermediate phase to the percentage of amorphous phase in the polished layer under the wetted state, as determined by pulsed nuclear magnetic resonance at 40°C, is 0.4 or more and 0.9 or less.

2. The abrasive pad according to claim 1, wherein the content of the amorphous phase in the abrasive layer, as determined by pulsed nuclear magnetic resonance at 40°C in the wet state, is 30.0% or more and 55.0% or less.

3. The abrasive pad according to claim 1, wherein the content of the intermediate phase in the abrasive layer, as determined by pulsed nuclear magnetic resonance at 40°C in the wet state, is 15.0% or more and 35.0% or less.

4. The abrasive pad according to claim 1, wherein the isocyanate-terminated prepolymer comprises constituent units derived from a polyisocyanate compound and constituent units derived from a high molecular weight polyol, wherein the constituent units derived from the high molecular weight polyol comprise at least constituent units derived from polyester diol and constituent units derived from polyoxytetramethylene diol.

5. The abrasive pad according to claim 4, wherein the average molecular weight of the polyester diols used to form the constituent units derived from polyester diols is 600 or more and 2500 or less.

6. The abrasive pad according to claim 4, wherein the constituent units derived from polyoxytetramethylene glycol are 30% by weight or more and 80% by weight or less relative to the constituent units derived from high molecular weight polyols.

7. The abrasive pad according to claim 4, wherein the polyurethane resin foam uses at least two isocyanate-terminated prepolymers as raw materials, at least one of the at least two isocyanate-terminated prepolymers contains the constituent unit derived from polyoxytetramethylene glycol, and the isocyanate-terminated prepolymer containing the polyoxytetramethylene glycol constituent unit has an NCO equivalent of 400 or more and 500 or less.

8. The abrasive pad according to claim 4, wherein the polyurethane resin foam uses at least two isocyanate-terminated prepolymers as raw materials, at least one of the at least two isocyanate-terminated prepolymers contains the constituent unit derived from polyester glycol, and the isocyanate-terminated prepolymer containing the polyester glycol constituent unit has an NCO equivalent of 550 or more and 700 or less.

9. An abrasive pad having an abrasive layer comprising a polyurethane resin foam, said polyurethane resin foam being made from isocyanate-terminated prepolymer and a hardener, wherein the abrasive pad, The value obtained by subtracting the percentage of intermediate phase in the polished layer measured by pulsed nuclear magnetic resonance at 40°C in the wet state from the percentage of intermediate phase in the dry state measured by pulsed nuclear magnetic resonance at 40°C is -2.0% or more and less than 2.0%. The value obtained by subtracting the percentage of amorphous phase in the polished layer measured by pulsed nuclear magnetic resonance at 40°C in the wet state from the percentage of amorphous phase in the polished layer measured by pulsed nuclear magnetic resonance at 40°C in the dry state is 2.0% or more and 5.7% or less.

10. The abrasive pad according to claim 9, wherein the proportion of crystalline phase in the abrasive layer, as determined by pulsed nuclear magnetic resonance at 40°C in the wet state, is smaller than the proportion of amorphous phase.

11. The abrasive pad according to claim 9, wherein the content of the amorphous phase in the abrasive layer, as determined by pulsed nuclear magnetic resonance at 40°C in the wet state, is 30.0% or more and 55.0% or less.

12. The abrasive pad according to claim 9, wherein the content of the amorphous phase in the abrasive layer, as determined by pulsed nuclear magnetic resonance at 40°C in the dry state, is 30.0% or more and 50.0% or less.

13. The abrasive pad of claim 9, wherein the isocyanate-terminated prepolymer comprises constituent units derived from a polyisocyanate compound and constituent units derived from a high molecular weight polyol, wherein the constituent units derived from the high molecular weight polyol comprise constituent units derived from polyester diol and constituent units derived from polyoxytetramethylene diol.

14. The abrasive pad according to claim 13, wherein the average molecular weight of the polyester diols used to form the constituent units derived from polyester diols is 600 or more and 2500 or less.

15. The abrasive pad according to claim 13, wherein the polyoxytetramethylene glycol constituent unit is 30% or more and 80% or less relative to the constituent unit derived from the high molecular weight polyol.

16. The abrasive pad according to claim 13, wherein the polyurethane resin foam uses at least two isocyanate-terminated prepolymers as raw materials, at least one of the at least two isocyanate-terminated prepolymers contains a constituent unit derived from polyoxytetramethylene glycol, and the isocyanate-terminated prepolymer containing the constituent unit derived from polyoxytetramethylene glycol has an NCO equivalent of 400 or more and 500 or less.

17. The abrasive pad of claim 13, wherein the polyurethane resin foam uses at least two isocyanate-terminated prepolymers as raw materials, at least one of the at least two isocyanate-terminated prepolymers comprising the constituent unit derived from polyester glycol, and the isocyanate-terminated prepolymer comprising the constituent unit derived from polyester glycol has an NCO equivalent of 550 or more and 700 or less.

Citation Information

Patent Citations

  • Multi-functional polishing pad

    JP2011040737A